Integrated process for the purification and immobilization of the envelope protein domain III of dengue virus type 2 expressed in Rachiplusia nu larvae and its potential application in a diagnostic assay - Smith, María Emilia (2017)
Dengue incidence has grown dramatically in the last years, with about 40% of the world population at risk of infection. Recently, a vaccine developed by Sanofi Pasteur has been registered, but only in a few countries. Moreover, specific antiviral drugs are not available. Thus, an efficient and accurate diagnosis is important for disease management. To develop a low-cost immunoassay for dengue diagnosis, in the present study we expressed the envelope protein domain III of dengue virus type 2 in Rachiplusia nu larvae by infection with a recombinant baculovirus. The antigen was expressed as a fusion to hydrophobin I (DomIIIHFBI) to easily purify it by an aqueous two-phase system (ATPS) and to efficiently immobilize it in immunoassay plates. A high level of recombinant DomIIIHFBI was obtained in R. nu, where yields reached 4.5 mg per g of larva. Also, we were able to purify DomIIIHFBI by an ATPS with 2% of Triton X-114, reaching a yield of 73% and purity higher than 80% in a single purification step. The recombinant DomIIIHFBI was efficiently immobilized in hydrophobic surface plates. The immunoassay we developed with the immobilized antigen was able to detect IgG specific for dengue virus type 2 in serum samples and not for other serotypes.